The Effect Of Psychological Safety And Learning Agility On Civil Servant Performance: The Mediating Role Of Innovative Work Behavior In The Indonesian Public Sector - Anindya Dwi Novitasari; Zainul Kisman (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
Public sector organizations are increasingly required to enhance performance and innovation amid bureaucratic reform and digital transformation. However, empirical evidence regarding the psychological mechanisms underlying civil servant performance remains limited, particularly in hierarchical public institutions. This study investigates the effect of psychological safety and learning agility on civil servant performance, with innovative work behavior as a mediating variable. A quantitative approach was employed using survey data collected from 167 civil servants at the Ministry of Villages and Development of Disadvantaged Regions, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that learning agility has a positive and significant effect on performance, whereas psychological safety does not directly influence performance. Both psychological safety and learning agility significantly enhance innovative work behavior. Innovative work behavior significantly improves performance and mediates the relationship between learning agility and performance, but not between psychological safety and performance. This study contributes to public sector human resource management literature by clarifying the behavioral mechanism linking adaptive learning capability and performance. The findings suggest that in bureaucratic contexts, psychological safety alone is insufficient to drive performance unless translated into innovative actions. Policy implications for strengthening adaptive learning and innovation ecosystems in public institutions are discussed.